HUBUNGAN ANTARA LIMA FAKTOR KEPRIBADIAN (BIG FIVE PERSONALITY) DENGAN KPU TRUST PEMILIH PEMILU 2024 - Rasyid, Irsyad Abdul; Akhrani, Lusy Asa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2021)
This research aims to know the corelation between big five personality (extraversion, neuroticism, conscinetiousness, agreeableness, & openness) and KPU trust. There was 548 respondens who participate in this research. Respondens are Indonesian citizens who have the right to vote and will participate in the next election in 2024. Respondens were collected by accidental sampling. Big five personality measured by Big Five Inventory 44-item Scale which has modificated by Ramdani (2012). KPU trust measured by KPU trust scale (Akhrani, 2019) which refers to Lewicki, McAllister, & Bies research in 1998. This research use stepwise method to analyse the data. Conscientiousness is the only trait which showed the correlation with KPU trust as the result of the stepwise method. Correlation coefficient shows at 0,107 (p<0,05) which means there is a weak correlation between conscientiousness and KPU trust.